STRUKTUR ELEMEN PENGEMBANGAN INDUSTRI KECIL JAMU - Kusnandar Kusnandar (Universitas Sebelas Maret, 2007)
Indonesia is known by its diversity and one of them is medicinal plants. Therefore, development of small-size medicinal plants based industry like jamu industry is strategic effort and must be well prepared. The result of this study used Interpretative Structural Modelling (ISM) technique were development system structural, clasification of elements which were based on its driver power level and dependency level and key elements of small-size jamu industry development.